System Control Holding Position on Quadcopter Using GPS with Waypoint - Widhianto, Trisno; Yudhana, Anton (Peneliti Teknologi Teknik Indonesia, 2023)
This study designs an autonomous quadcopter system that can work in outdoor areas using a waypoint and quadcopter system so that it can fly without being controlled to complete a given mission with accuracy that has a low offside value. The tests carried out were divided into 3 tests using 3 different missions using Post Hold flight mode and a height of 5 m, on each mission there were 3 waypoints with each waypoint distance of 10 m which later on each waypoint would perform a Holding Position. at each waypoint point and see the error value generated based on the waypoint point by calculating the Latitude and Longitude values between the vehicle and the waypoint point so as to get the error value between the vehicle and the waypoint point and then make a comparison with measurements using a measuring instrument at each waypoint point in carrying out missions.